Meningkatkan Hasil Belajar PAKBP dengan Model PBL Materi Perempuan dan Laki-Laki Diciptakan sebagai Citra Allah Melalui Metode Dinamika Kelompok Fase C Kelas V SDN Mangkubumen Kidul Surakarta - Yohanes Pratamto Henri (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Catholic Religious Education at SDN Mangkubumen Kidul Surakarta City is carried out with an Independent curriculum. As is known, the learning method is a means of interaction between teachers and students in learning activities towards the objectives, types, and learning materials as well as the teacher's ability to understand and implement the method. In this study, the researcher chose the Group Dynamics learning method to solve the existing problem, namely trying to research whether the use of Group Dynamics learning can improve student learning outcomes carried out by classroom action research. The title of this study is